2012
DOI: 10.1097/hjh.0b013e32834f98a0
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular cuffs may overestimate blood pressure in individuals with large conical arms

Abstract: In obese people, the upper arm may have a pronounced tronco-conical shape and cylindrical cuffs may overestimate BP. Tronco-conical cuffs should be used for BP measurement in individuals with large arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 12 publications
1
91
3
Order By: Relevance
“…Canadian guidelines recommend at least 3 visits to classify individual patients with borderline levels of hypertension. 396 Finally, it is well recognized that arm shape, 397 cuff size selection, and operator training affect these measurements. Therefore, training of personnel is crucial, and recommendations and guidelines have been issued in this regard.…”
Section: Bp Variability and Assessment Of Ssbpmentioning
confidence: 99%
“…Canadian guidelines recommend at least 3 visits to classify individual patients with borderline levels of hypertension. 396 Finally, it is well recognized that arm shape, 397 cuff size selection, and operator training affect these measurements. Therefore, training of personnel is crucial, and recommendations and guidelines have been issued in this regard.…”
Section: Bp Variability and Assessment Of Ssbpmentioning
confidence: 99%
“…Actually, Palatini and colleagues examined whether the shape of the upper arm and the cuff affected BP. Results showed that troncoconical cuff fit better on those with large mid-AC than rectangular cuffs [23].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, our study did not specifically assess the possible impact of conical shape arms on the accuracy of BP measurement, where the use of rectangular cuffs may cause BP overestimation, even if the cuff range appears adequate for the arm circumference. 31 …”
Section: Discussionmentioning
confidence: 99%